PEMETAAN INFORMASI SEBARAN BIDANG ILMU PADA PENELITIAN SKRIPSI FAKULTAS PERIKANAN DAN ILMU KELAUTAN IPB LULUSAN TAHUN 2014-2018 BERDASARKAN STANDAR UNIVERSAL DECIMAL CLASSIFICATION - Abdul Rahman Saleh; Deden Himawan (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
Introduction. Fish and its by-products are is one of important food commodities. It is hoped that with the culture of eating fish, the Indonesian people can suppress cases of malnutrition, stunting and several other food cases. Indonesia's fish production target in 2019 will reach 38.3 million tons coming from capture fisheries, aquaculture and seaweed. All efforts to increase productivity can not be separated from various research conducted by researchers, lecturers, and students. To find out the distribution of research topics in the fisheries field, a study was conducted.Methods. This research is a combination of qualitative and quantitative research (mixed methods) with descriptive analysis methods. Data was taken based on purposive sampling from student's report from 2014 to 2018.Analysis. The data came from the student's final report of the students of the Faculty of Fisheries and Marine Sciences IPB who graduated from 2014 to 2018 totaling 1,826 titles. Data is grouped, tabulated and processed using descriptive analysis that is completed by interviews with experts.Results and Discussion. The Student's final report of the BDP Department was 399 titles (21.85%), the MSP Department was 383 titles (20.97%), the THP Department was 374 titles (20.48%). ITK Department as many as 357 research titles (19.55%), PSP Department as many as 313 research titles (17.14%). The most FPIK student research is in the applied science group (1313 titles or 71.91%), pure science (432 titles or 23.17%), social and economic sciences (86 titles or 4.71%), and the most a little is the general group of 4 titles (0.22%). Catfish is the type of fish most studied, as many as 64 studies, while fish of baung, lelawak, uceng, and tambakan are the types of fish that are the least studied, each with only 1 study. Whereas in the type of sea fish/brackish, eel fish is the most studied (21 studies). The fish of baronang and swanggi are the fish that the least studied. The most productive lecturer in guiding the student was Agoes Mardiono Jacoeb with 81 students.Conclusions and suggestions. The fields of study of FPIK students consisted of two major groups namely those related to fishery commodities (29.90%) and non-fisheries commodities (70.10%). Road maps need to be made so that research in the field of fisheries is directed and does not cluster in certain fields of science or commodities.